Total angular momenta of high-lying odd levels of U I at ∼ 4 eV using resonance ionization laser polarization spectroscopy. (February 2018) - Rath, Asawari D.; Kundu, S.; Ray, A.K.
Highlights: Total angular momenta J of high lying odd-parity energy levels of U I near ∼ 4 eV were determined by resonance ionization laser polarization spectroscopy. There was excellent agreement between the experimental observations and simulations for levels with known J. J angular momenta of 15 U I levels were unambiguously assigned. This technique provides a simple yet reliable method for J-value determination of atomic levels. Abstract: Laser induced photoionization of atoms shows significant dependence on the choice of polarizations of lasers. In multi-step, multi-photon excitation and subsequent ionization of atoms different polarization combinations of the exciting lasers lead to distinctly different ion yields. This fact is exploited in this work to determine total angular momenta of odd-parity energy levels of U I lying at ∼ 4 eV from its ground level using resonance ionization laser polarization spectroscopy in time of flight mass spectrometer. These levels are populated by two-step resonant excitation using two pulsed dye lasers with preset polarizations of choice followed by nonresonant ionization by third laser. The dependence of ionization yield on specific polarizations of the first two lasers is studied experimentally for each level under consideration. This dependence when compared to simulations makes possible unambiguous assignment of J angular momenta to these levels.